Simplified alternative to model the kinetics of an in-situ combustion process (2018)
In situ combustion (ISC) is an enhanced oil recovery (EOR) technique with great potential for application in heavy and extra-heavy oil fields; however, its implementation has been limited due to the high degree of uncertainty associated with its development at the field scale. Considering the level of complexity of the ISC process compared to other EOR / IOR techniques, to evaluate the technical feasibility of ISC in a specific reservoir will take far more complex screening methods and laboratory testing. Among the tests required to evaluate ISC include the kinetic cell tests, which are aimed at determining the oxidative behavior of the rock-fluid system under study, and in turn, allow obtaining a kinetic model that represents, by means of numerical modeling, the performance of the ISC process obtained experimentally in combustion tube tests. Based on the above, in the present work, the results obtained from the adjustment of a combustion tube test were compared using the Arrhenius and non- Arrhenius methodologies, evidencing significant differences in the computation time and in the residual oil saturation values in the porous medium after the implementation of the ISC process.